Dispatchable Renewables: Selecting a Right Pathway (Global Journals of Research in Engineering, 2024)
Clean Grid readiness is a major objective of Canada s Clean Grid 2035 efforts and commitment to make all electricity generation in the country carbon net-zero Making all the sources of electricity in power grids clean would be a tremendous step in Canada s energy transition and low carbon economy growth Deploying on a very large scale variable renewables such as wind and solar in Canada requires an extremely significant power dispatchability effort allowing the country s power grids to maintain their reliability Dispatchable generation refers to controllable and flexible sources of electricity that can promptly respond to demand at the request of power grid operators The Clean Grid 2035 commitment assumes that all existing and new power dispatchability sources in Canada backing up variable renewables operations are clean Choosing to have the renewable segment of clean dispatchability sources lead in Canada s Clean Grid efforts and creating renewable dispatchable fleets the clean power generation fleets that will make all variable renewables in the country dispatchable Canada s extremely strong reservoir-based dispatchable hydro power generation in Newfoundland and Labrador Quebec and Manitoba can participate in these fleets to back up variable renewables growth in the country Canada s unique geothermal power generation in the Pacific Rim including the regions of northeastern British Columbia and southern Yukon northern Alberta and southern Northwest Territories constitutes very high potential for highly dispatchable electricity generation to participate in renewable dispatchable fleets The proposed approach to using hydropower as a variable dispatchability reserve for Eastern Canada and combining hydropower and geothermal power as dispatchability reserves for Western Canada will make variable renewables dispatchable upgrading all power grids in Canada to 100 Clean Grid readiness by 2035 and maintaining this Clean Grid commitment in 2050 and beyond Using dispatchable hydropower and geothermal power together with wind and solar power in Renewable Dispatchable Fleets would make all renewable capacity dispatchable establishing leading clean dispatchability practices in North America To agree on Renewable Dispatchable Fleets deployment and existing Renewable Dispatchability Reserves commitments from the provinces owning and operating large scale reservoir-based hydro power plants Canada s electric federalism concept and approach should be demonstrated efficiently and promptly
Keywords: carbon net zero; electric federalism; clean grid readiness; variable renewables; dispatchability reserves; hydro power